Multifaceted Intervention by the Hsp90 Inhibitor Ganetespib (STA-9090) in Cancer Cells with Activated JAK/STAT Signaling - David A. Proia; Kevin P. Foley; Tim Korbut; Jim Sang; Don Smith; Richard C. Bates; Yuan Liu; Alex Rosenberg; Dan Zhou; Keizo Koya; James Barsoum; Ronald K. Blackman (2011)
There is accumulating evidence that dysregulated JAK signaling occurs in a wide variety of cancer types. In particular, mutations in JAK2 can result in the constitutive activation of STAT transcription factors and lead to oncogenic growth. JAK kinases are established Hsp90 client proteins and here we show that the novel small molecule Hsp90 inhibitor ganetespib (formerly STA-9090) exhibits potent in vitro and in vivo activity in a range of solid and hematological tumor cells that are dependent on JAK2 activity for growth and survival. Of note, ganetespib treatment results in sustained depletion of JAK2, including the constitutively active JAK2(V617F) mutant, with subsequent loss of STAT activity and reduced STAT-target gene expression. In contrast, treatment with the pan-JAK inhibitor P6 results in only transient effects on these processes. Further differentiating these modes of intervention, RNA and protein expression studies show that ganetespib additionally modulates cell cycle regulatory proteins, while P6 does not. The concomitant impact of ganetespib on both cell growth and cell division signaling translates to potent antitumor efficacy in mouse models of xenografts and disseminated JAK/STAT-driven leukemia. Overall, our findings support Hsp90 inhibition as a novel therapeutic approach for combating diseases dependent on JAK/STAT signaling, with the multimodal action of ganetespib demonstrating advantages over JAK-specific inhibitors.